2011
DOI: 10.1051/kmae/2011028
|View full text |Cite
|
Sign up to set email alerts
|

Using consumption rate to assess potential predators for biological control of white perch

Abstract: Key-words:biological control, predation, consumption rate, white perch, Morone americana Control of undesirable fishes is important in aquatic systems, and using predation as a tool for biological control is an attractive option to fishery biologists. However, determining the appropriate predators for biological control is critical for success. The objective of this study was to evaluate the utility of consumption rate as an index to determine the most effective predators for biological control of an invasive … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…White Perch abundance has been directly linked to predation (Margulies 1990;Hartman and Margraf 1992;Vrtiska et al 2003). Gosch and Pope (2011) found that predation may increase stunting in White Perch populations if large predators remove older, larger (rather than younger, smaller) individuals from the population, thereby decreasing the overall size structure. Contrary to this pattern, Largemouth Bass in the present study did not consume many White Perch.…”
Section: Discussionmentioning
confidence: 99%
“…White Perch abundance has been directly linked to predation (Margulies 1990;Hartman and Margraf 1992;Vrtiska et al 2003). Gosch and Pope (2011) found that predation may increase stunting in White Perch populations if large predators remove older, larger (rather than younger, smaller) individuals from the population, thereby decreasing the overall size structure. Contrary to this pattern, Largemouth Bass in the present study did not consume many White Perch.…”
Section: Discussionmentioning
confidence: 99%
“…Our conclusions raise questions about the best method to mitigate the potential impact of White Perch invasions. For systems where White Perch have already been introduced, control or eradication efforts through manual removals or stocking of potential predators have been unsuccessful (Vrtiska et al 2003;Gosch and Pope 2011). Therefore, we recommend that biologists concentrate on education and regulatory efforts to stop further introductions of White Perch in any effort to protect and maintain White Bass fisheries (Johnson et al 2009).…”
Section: White Perchmentioning
confidence: 99%
“…Species composition and size‐classes of predatory fish in a community can have important effects on predation levels of larval prey (Chalcraft & Resetarits, ; Parke et al ., ). Prey preferences (Silbernagel & Sorenson, ; Reiss et al ., ), foraging efficiencies (Scharf et al ., ) and consumption rates (Gosch & Pope, ) can vary greatly among predators. Recognition of certain species as important predators of larval fish can inform management decisions about harvest regulations, targeted removals, biological controls, or other strategies of predator control to improve recruitment of a target species (Carpenter & Mueller, ).…”
Section: Introductionmentioning
confidence: 99%